Evaluation of risk factors' importance on adverse pregnancy and neonatal outcomes in women aged 40 years or older - Gunilla Sydsjö; Malin Lindell Pettersson; Marie Bladh; Agneta Skoog Svanberg; Claudia Lampic; Elizabeth Nedstrand (BMC, 2019)
Abstract Background Women of advanced age (40 years or older) are generally, at risk for pregnancy and delivery related problems. In addition, there is limited knowledge on being of advanced age and having been given Assisted Reproductive Treatment (ART) and its association with negative obstetric outcomes. Therefore, data from the Swedish Medical Birth Register was used to investigate pregnancy and neonatal outcomes for women aged 40 or more who had given birth. The secondary aim was to compare the obstetric outcomes of women who had used ART and women who had not undergone ART while adjusting for marital status across the age groups. Method Women of advanced age who had given birth in Sweden during 2007-2012 formed the index group, n = 37,558; a reference group of women comprised 71,472 women under the age of 40. An additional subgroup of women aged 45 or older when giving birth was also formed, n = 2229. The obstetric and neonatal data for all the women was derived from national register data. Results Women of advanced age were more often single, had undergone ART, and more often experienced adverse obstetric outcomes than did younger women. The neonate's health was also more often adversely affected expressed as being born with low birth weight and Small for Gestational Age (SGA), having lower Apgar scores, and having more health problems during the first week compared to the reference group. Conclusions Women who are approaching the upper limit of fecundity are at greater risk for having children who are preterm and SGA. The adverse effects of being preterm and SGA may have negative long-term effects, not only on the children but also on the mothers. This needs to be addressed more frequently in a clinical setting when advising women of all ages on pregnancy and ART treatment.